A truck full of money - Kidder, Tracy (Random House, 2016)
"Like Paul Farmer in Mountains Beyond Mountains, Paul English grew up poor, in working-class Boston, but as Tracy Kidder writes, he had "a mind for the age that was coming." Brilliant, reckless, endlessly energetic, Paul English, after Kayak sold for $2 billion, asked himself: What comes next? Start another company? Use his new wealth to make a difference in the world? With a riveting, page-turning narrative and unmatched storytelling skill, Kidder casts a fresh and critical eye on how new technologies and start-ups, new money, are reshaping our culture"--